Perbandingan Implementasi Smart Campus di Perguruan Tinggi Indonesia - Koesanto, Stefani Made Ayu Artharini; Wiradharma, Gunawan; Prasetyo, Mario Aditya; Ningrum, Karina Pramita (Jayapangus Press, 2025)
This study aims to analyze the implementation of smart campuses across various higher education institutions in Indonesia and to identify the challenges and strategies involved in supporting the three pillars of higher education (tridarma). Employing a descriptive qualitative approach, data were collected through semi-structured interviews with six informants consisting of lecturers, students, and IT experts from both academic universities and vocational institutions. The findings indicate significant variation in the adoption of smart campus technologies, influenced by infrastructure readiness, digital literacy levels, and institutional priorities. Academic universities tend to adopt administrative and digital learning systems more rapidly, while vocational institutions focus on the practical application of technology for industrial training. The main challenges identified include limited access to internet infrastructure and digital devices, as well as low digital literacy, particularly among senior faculty and students. In response, many institutions have initiated digital literacy training and the development of integrated information systems. This study highlights the need for a standardized and adaptable smart campus framework tailored to each institution’s context. Furthermore, collaboration between universities and technology providers is considered essential for accelerating campus-wide digital transformation. The results of this research are expected to serve as a reference for policymakers and institutional leaders in formulating more effective, sustainable, and inclusive strategies for smart campus development in the era of digital transformation in higher education.